Penyelesaian Tindak Pidana Yang Terjadi Di Atas Tanah Sengketa - Erdianto ' (Fakultas Hukum Universitas Riau, 2013)
Criminal law is s the ultimate remedy, because it should be the completion of the criminal case is concerned with disputes in civil law especially land disputes, should not be processed prior to a decision that remains on civil cases, however, in practice, the situation is difficult to implement because many civil disputes concerning land ownership carried with letters of doubtful ownership.